Damp-proof and compression-resistant corrugated carton for packaging and preparation method thereof

By using double-layer coating technology on corrugated cartons and using the combination of base coating and waterproof coating, the problem of insufficient compressive performance and moisture resistance of corrugated cartons is solved, and better water resistance, compressive resistance and wear resistance are achieved.

CN120211146AInactive Publication Date: 2025-06-27HUAIAN FOSTER PACKAGING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510443534.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-06-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional corrugated cartons have poor compressive resistance and moisture resistance, which are prone to absorb water and deformity, resulting in reduced performance. In the prior art, the bonding force between the coating and the paper base is poor, local peeling or microcracks are prone to occur, and waterproof and compressive resistance is reduced.

Method used

Using double-layer coating technology, the base coating is first coated. The coating contains moisture-sensitive color-changing pigment, which can serve as an early warning when the waterproof layer fails. The base coating contains silicon acrylic emulsion and acrylic film-forming emulsion, which can form a strong combination with the cellulose base of the paper substrate, improving the uniformity and binding strength of the waterproof coating. Add acrylate core-shell emulsion and modified composite filler to the waterproof coating to improve compressive resistance and wear resistance.

Benefits of technology

The moisture-proof and compressive performance of corrugated cartons has been improved, the coating bonding force has been enhanced, the waterproofness and compressive resistance have been significantly improved, and it has good wear resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of coatings for corrugated cartons, and discloses a moisture-proof and pressure-resistant corrugated carton for packaging and a preparation method thereof. The preparation method comprises the following steps: bonding the surface paper, the inner paper, the core paper and the corrugated paper which is processed into wave-shaped corrugations, so as to obtain the moisture-proof and compression-resistant corrugated carton for packaging; the surface paper, the inner paper, the core paper and the corrugated paper processed into the wave-shaped corrugations are coated with priming paint and waterproof paint before being bonded; the priming paint is prepared from the following raw materials in parts by mass: 20 to 30 parts of silicone acrylic emulsion, 30 to 40 parts of acrylic acid film-forming emulsion, 3 to 5 parts of modified composite filler, 15 to 25 parts of humidity-sensitive color-changing pigment and 1 to 2 parts of defoaming agent; the waterproof coating is prepared from the following raw materials in parts by mass: 30 to 40 parts of silicone acrylic emulsion, 8 to 10 parts of acrylic acid film-forming emulsion, 20 to 30 parts of acrylate core-shell emulsion, 20 to 30 parts of modified composite filler, 1 to 2 parts of photoinitiator and 1 to 2 parts of defoaming agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings for corrugated paper boxes, and discloses a corrugated paper box for moisture-proof and pressure-resistant packaging and a preparation method thereof. Background Art

[0002] Corrugated cardboard is a paper composite packaging material, which is made of corrugated core paper and inner and outer paper bonded together. It has the advantages of good cushioning performance, light weight and firmness, sufficient raw materials, low cost, and recyclability. It is an indispensable packaging container in production and life and is widely used in various industries.

[0003] However, the traditional corrugated paper boxes have poor compression and moisture resistance, and are prone to water absorption and deformation during storage, resulting in a significant decline in various performances. In the prior art, a coating with compression and moisture resistance is applied to the surface of the paper box to improve its performance, but the coating has poor bonding with the paper base, which is prone to local peeling or microcracks, resulting in reduced waterproof and compression resistance; on the other hand, the existing moisture-proof paper boxes lack the ability to monitor humidity changes in real time. In summary, it is of great significance to study a corrugated paper box for packaging with good moisture and compression resistance and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a moisture-proof and pressure-resistant corrugated paper box for packaging and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging: comprising the following steps: bonding face paper, lining paper, core paper and corrugated paper processed into corrugated paper to obtain a moisture-proof and pressure-resistant corrugated paper box for packaging; coating the face paper, lining paper, core paper and corrugated paper processed into corrugated paper with a primer and a waterproof coating before bonding;

[0006] The primer coating comprises the following raw materials, calculated by weight: 20 to 30 parts of silicone-acrylic emulsion, 30 to 40 parts of acrylic film-forming emulsion, 3 to 5 parts of modified composite filler, 15 to 25 parts of moisture-sensitive color-changing pigment, and 1 to 2 parts of defoaming agent;

[0007] The waterproof coating comprises the following raw materials, calculated by mass: 30 to 40 parts of silicone-acrylic emulsion, 8 to 10 parts of acrylic film-forming emulsion, 20 to 30 parts of acrylate core-shell emulsion, 20 to 30 parts of modified composite filler, 1 to 2 parts of photoinitiator 1173, and 1 to 2 parts of defoaming agent.

[0008] Preferably, the primer coating is cured after being applied. The curing process is curing at 80 - 90 °C for 3 - 4 h and then at 120 - 130 °C for 3 - 4 h, followed by applying the waterproof coating. The curing process of the waterproof coating is: curing at 50 - 60 °C for 0.5 - 1 h, ultraviolet light irradiation for 20 - 40 s, and then curing at 120 - 130 °C for 3 - 4 h.

[0009] Preferably, the silicone-acrylic emulsion is Jiyesheng A00776; the acrylic film-forming emulsion is the Joncryl-FLX5000 acrylic film-forming emulsion from BASF, Germany.

[0010] Preferably, the preparation method of the humidity-sensitive color-changing pigment is as follows: Take 1 - 2 parts of cresol red color-changing agent and 100 - 150 parts of boric acid, mix and grind evenly, add 70 - 100 parts of silica gel, grind thoroughly until the color no longer changes, pass through a 100-mesh sieve and dry to obtain the base pigment; Take 10 - 15 parts of nano-silica, 30 - 50 parts of ethanol, 60 - 100 parts of water, stir and react at 70 °C for 2 - 3 h, add 50 - 80 parts of the base pigment, and stir at 40 - 50 °C for 3 - 4 h to obtain the humidity-sensitive color-changing pigment.

[0011] Preferably, the preparation of the modified composite filler includes the following steps: Take cetyltrimethylammonium bromide, trimethylethylammonium bromide, and sodium-based montmorillonite, add to water and perform ultrasonic treatment for 0.5 - 1 h, heat up to 55 - 90 °C, perform ultrasonic treatment for 10 - 20 h, wash, filter by suction, and dry to obtain the modified montmorillonite; Take the modified montmorillonite, add ethanol, stir at 20 - 25 °C for 2 - 3 h, add tetraethoxysilane, stir at 20 - 25 °C for 2 - 3 h, adjust the pH to 5 - 6, stir at 20 - 25 °C for 2 - 3 h, filter and wash to obtain the modified composite filler.

[0012] Preferably, the modified montmorillonite includes the following raw materials, by mass: 0.1 - 0.2 parts of cetyltrimethylammonium bromide, 0.2 - 0.3 parts of trimethylethylammonium bromide, 0.8 - 1.2 parts of sodium-based montmorillonite, 10 - 15 parts of water; the modified composite filler includes the following raw materials, by mass: 1 - 2 parts of modified montmorillonite, 20 - 30 parts of ethanol, 20 - 30 parts of tetraethoxysilane.

[0013] Preferably, the preparation of the acrylate core-shell emulsion includes the following steps: Prepare a core pre-emulsion with n-butyl acrylate, methyl methacrylate, modified composite filler, and an aqueous emulsifier solution; Prepare a shell pre-emulsion with n-butyl acrylate, methyl methacrylate, fluorine-containing monomer, modified composite filler, crosslinking monomer, and an aqueous emulsifier solution; Prepare the acrylate core-shell emulsion with the core pre-emulsion and the shell pre-emulsion.

[0014] Preferably, the core pre-emulsion liquid comprises the following raw materials by mass: 10-15 parts of n-butyl acrylate, 1-2 parts of methyl methacrylate, 0.5-1 part of modified composite filler; the shell pre-emulsion liquid comprises the following raw materials by mass: 1-2 parts of n-butyl acrylate, 5-6 parts of methyl methacrylate, 3-4 parts of fluorine-containing monomer, 1-1.2 parts of modified composite filler, 0.2-0.3 part of cross-linking monomer.

[0015] Preferably, the preparation steps of the acrylate core-shell emulsion are as follows: Take 0.2-0.3 part of polyethylene glycol octyl phenyl ether, 0.3-0.4 part of sodium dodecyl sulfate, and 15-20 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts by volume; Drop 10-15 parts of n-butyl acrylate, 1-2 parts of methyl methacrylate, and 0.5-1 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion liquid; Take 1-2 parts of n-butyl acrylate, 5-6 parts of methyl methacrylate, 3-4 parts of fluorine-containing monomer, 1-1.2 parts of modified composite filler, and 0.2-0.3 part of cross-linking monomer methyl methacrylate and drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion liquid; Dissolve 0.06-0.1 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution; Dissolve 0.1-0.2 part of potassium persulfate in 6-10 parts of water to obtain an initiator aqueous solution; Under nitrogen protection, mix the buffer aqueous solution, 1.5-2 parts of the initiator aqueous solution and 2 / 5 volume of the core pre-emulsion liquid evenly, heat up to 60-65 °C, and keep warm for 30-60 min when a large amount of blue light appears in the emulsion to obtain a seed emulsion; Drop the remaining core pre-emulsion liquid and 1.5-2 parts of the initiator aqueous solution into the seed emulsion within 1 h, heat up to 65-70 °C after dropping, and keep warm for 30-60 min to obtain a core emulsion; Add the remaining initiator aqueous solution and the shell pre-emulsion liquid to the core emulsion within 1 h, heat up to 80 °C, keep warm for 30-60 min, cool, adjust the pH to neutral, and pass through a 200-mesh sieve to obtain the acrylate core-shell emulsion.

[0016] Preferably, the preparation of the fluorine-containing monomer comprises the following steps: Add pentaerythritol triacrylate and potassium carbonate to water, stir and disperse, add o-trifluoromethylbenzoyl chloride at 0-5 °C, stir and disperse, heat up to 20-30 °C and stir for 20-30 h, remove the solvent to obtain the fluorine-containing monomer.

[0017] Preferably, the fluorine-containing monomer comprises the following raw materials by mass: 28-33 parts of pentaerythritol triacrylate, 10-15 parts of potassium carbonate, 15-20 parts of o-trifluoromethylbenzoyl chloride.

[0018] Preferably, the coating thickness of the primer coating is 5-8 μm; the coating thickness of the waterproof coating is 20-30 μm.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: A double-layer coating is adopted. First, the primer coating is applied. The primer coating contains a humidity-sensitive discoloring pigment, which is applied inside the waterproof coating. When the waterproof layer fails, discoloration will occur, playing a warning role; the primer layer contains a silicone-acrylic emulsion and an acrylic film-forming emulsion, and forms ionic bonds and covalent bonds with the cellulose group on the paper substrate, with good bonding force and good film-forming flatness, which helps the application of the next layer of waterproof coating to obtain a more uniform coating to improve waterproof performance; at the same time, the primer layer also has a certain degree of waterproof performance. First, it is applied, and after curing, the next layer of waterproof coating is applied, which can reduce the problem of excessive stress and deterioration of the coating surface quality caused by too thick a single-layer waterproof coating.

[0020] The waterproof coating includes an acrylate core-shell emulsion and a modified composite filler. The addition of the acrylic core-shell emulsion can improve the compressive strength and wear resistance. The fluorine-containing monomer is pentaerythritol triacrylate modified by o-trifluoromethylbenzoyl chloride. On the one hand, monomers containing multiple double bonds are introduced, which can improve the crosslinking degree of the shell to improve mechanical properties. On the other hand, fluorine is introduced to improve hydrophobicity and make the whole negatively charged, interact with the modified composite filler in the waterproof coating to improve dispersion, and can also interact with the modified composite filler in the primer layer to improve the bonding force between the two layers, thereby improving the coating quality; the preparation method of the modified composite filler is as follows: First, sodium montmorillonite is intercalated with cetyltrimethylammonium bromide and trimethylethylammonium bromide to obtain modified montmorillonite, and then treated with tetraethoxysilane to load silica; the alkyl long chain of cetyltrimethylammonium bromide expands the montmorillonite layer spacing on the one hand to improve dispersion, and improves hydrophobicity on the other hand. Trimethylethylammonium bromide introduces double bonds into montmorillonite, improves its dispersion in the coating, and can be crosslinked under the action of a photoinitiator to improve the crosslinking degree, so as to strengthen the interlayer bonding force and the compressive strength and wear resistance of the coating; the surface-loaded silica further improves hydrophobicity and mechanical properties, and improves the compatibility with the coating itself; this modified composite filler is added to both layers of the coating, which helps to improve the interlayer adhesion; the thicknesses of the above two layers of coatings need to be controlled to ensure the balance of flatness, waterproofness, compressive strength, and wear resistance. Detailed implementation mode

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0022] It should be noted that there are no special restrictions on the purchasing manufacturers of all raw materials involved in the present invention. Exemplarily, they include: Cresol Red color-changing agent (CAS: 1733-12-6); Boric acid (CAS: 10043-35-3); Silica gel (Hubei Guangao GA2242); Nano-silica (Manli ML-SiO2-N20); Ethanol (CAS: 64-17-5); Silicon-acrylic emulsion (Jiyesheng A00776); Acrylic film-forming emulsion (BASF Joncryl-FLX5000, Germany); Defoaming agent (XIAMETER AFE-1520); Cetyltrimethylammonium bromide (CAS: 57-09-0); Trimethylethylammonium bromide (CAS: 10603-92-6); Sodium-based montmorillonite (Xianfeng Nano 103635); Tetraethoxysilane (CAS: 78-10-4); Pentaerythritol triacrylate (CAS: 3524-68-3); Potassium carbonate (anhydrous potassium carbonate, CAS: 584-08-7); 2-(Trifluoromethyl)benzoyl chloride (CAS: 312-94-7); Polyethylene glycol octylphenyl ether (Triton X-100, LMAI Bio LM80089C); Sodium dodecyl sulfate (CAS: 151-21-3); Sodium bicarbonate (CAS: 144-55-8); Potassium persulfate (CAS: 7727-21-1); Photoinitiator 1173 (CAS: 7473-98-5);

[0023] Unless otherwise specified, the following are all in parts by mass or mass ratio;

[0024] Preparation method of humidity-sensitive color-changing coating: Take 1 part of Cresol Red color-changing agent and 100 parts of boric acid, mix and grind evenly, add 80 parts of silica gel, fully grind until the color no longer changes, sieve through a 100-mesh sieve and dry to obtain the base pigment; Take 12 parts of nano-silica, 40 parts of ethanol, 80 parts of water, stir and react at 70 °C for 2 h, add 70 parts of the base pigment, and stir at 40 °C for 4 h to obtain the humidity-sensitive color-changing pigment;

[0025] Example 1: S1: Take 0.1 part of cetyltrimethylammonium bromide, 0.3 part of trimethylethylammonium bromide, and 1 part of sodium-based nano-montmorillonite, add to 15 parts of water and ultrasonically treat for 1 h, heat up to 80 °C, ultrasonically treat for 18 h, wash, filter by suction, and dry to obtain the modified montmorillonite; Take 2 parts of the modified montmorillonite, add to 30 parts of ethanol, stir at 20 °C for 2 h, add 25 parts of tetraethoxysilane, stir at 20 °C for 3 h, adjust the pH to 5 with hydrochloric acid, stir at 20 °C for 2 h, filter and wash to obtain the modified composite filler;

[0026] S2: Take 25 parts of silicon-acrylic emulsion, 35 parts of acrylic film-forming emulsion, 20 parts of humidity-sensitive color-changing pigment, 5 parts of the modified composite filler, and 1 part of defoaming agent, mix evenly to obtain the primer coating;

[0027] S3: Add 30 parts of pentaerythritol triacrylate and 12 parts of potassium carbonate into water, stir and disperse. Add 16 parts of o-(trifluoromethyl)benzoyl chloride at 3°C, stir and disperse, then raise the temperature to 25°C and stir for 24 h. Remove the solvent to obtain a fluorine-containing monomer. Take 0.2 part of polyethylene glycol octyl phenyl ether, 0.3 part of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts according to the amount. Drop 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, and 0.6 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion. Take 1 part of n-butyl acrylate, 6 parts of methyl methacrylate, 4 parts of fluorine-containing monomer, 1 part of modified composite filler, and 0.2 part of cross-linking monomer methacrylic acid and drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion. Dissolve 0.08 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution. Dissolve 0.15 part of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution. Under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution, and 2 / 5 volume of the core pre-emulsion evenly, raise the temperature to 60°C. When a large amount of blue light appears in the emulsion, keep it warm for 40 min to obtain a seed emulsion. Drop the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution into the seed emulsion within 1 h, raise the temperature to 65°C after dropping, and keep it warm for 30 min to obtain a core emulsion. Add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion within 1 h, raise the temperature to 80°C, keep it warm for 60 min, cool, adjust the pH to neutral, and pass through a 200-mesh sieve to obtain an acrylate core-shell emulsion.

[0028] S4: Take 40 parts of silicone-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 25 parts of acrylate core-shell emulsion, 25 parts of modified composite filler, 1 part of photoinitiator 1173, and 1 part of defoamer, mix evenly to obtain a waterproof coating.

[0029] S5: Bond the face paper, inner paper, core paper, and corrugated paper processed into corrugated shape to obtain a corrugated cardboard box for moisture-proof and compression-resistant packaging; before bonding, the face paper, inner paper, core paper, and corrugated paper processed into corrugated shape are all first coated with a primer coating, with a coating thickness of 6 μm, cured at 90°C for 3 h and at 130°C for 3 h, then coated with a waterproof coating, with a coating thickness of 25 μm, cured at 60°C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120°C for 3 h.

[0030] Example 2: S1: Take 0.2 parts of cetyltrimethylammonium bromide, 0.2 parts of trimethylethenylammonium bromide, and 1.2 parts of sodium-based nanometer montmorillonite, add them to 15 parts of water, ultrasonically treat for 1 h, heat up to 80 °C, ultrasonically treat for 18 h, wash, filter by suction, and dry to obtain modified montmorillonite; Take 2 parts of modified montmorillonite, add 30 parts of ethanol, stir at 20 °C for 2 h, add 20 parts of tetraethoxysilane, stir at 20 °C for 3 h, adjust the pH to 5 with hydrochloric acid, stir at 20 °C for 2 h, filter and wash to obtain modified composite filler;

[0031] S2: Take 30 parts of silicone-acrylic emulsion, 30 parts of acrylic film-forming emulsion, 25 parts of humidity-sensitive discoloring pigment, 3 parts of modified composite filler, and 1 part of defoaming agent, mix evenly to obtain the primer coating;

[0032] S3: Add 33 parts of pentaerythritol triacrylate and 15 parts of potassium carbonate to water, stir and disperse, add 20 parts of o-trifluoromethylbenzoyl chloride at 3 °C, stir and disperse, heat up to 25 °C and stir for 24 h, remove the solvent to obtain a fluorine-containing monomer; Take 0.2 parts of polyethylene glycol octyl phenyl ether, 0.3 parts of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts according to the amount; Drop 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, and 0.5 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion; Take 2 parts of n-butyl acrylate, 6 parts of methyl methacrylate, 3 parts of fluorine-containing monomer, 1 part of modified composite filler, and 0.2 part of cross-linking monomer methacrylic acid and drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion; Dissolve 0.08 parts of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution; Dissolve 0.15 parts of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution; Under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution and 2 / 5 volume of the core pre-emulsion evenly, heat up to 60 °C, when a large amount of blue light appears in the emulsion, keep warm for 40 min to obtain a seed emulsion; Drop the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution into the seed emulsion, finish dropping in 1 h, heat up to 65 °C after dropping, keep warm for 30 min to obtain a core emulsion; Add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion, finish dropping in 1 h, heat up to 80 °C, keep warm for 60 min, cool and adjust the pH to neutral, and pass through a 200-mesh sieve to obtain an acrylate core-shell emulsion;

[0033] S4: Take 35 parts of silicone-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 30 parts of acrylate core-shell emulsion, 25 parts of modified composite filler, 1 part of photoinitiator 1173, and 1 part of defoaming agent, mix evenly to obtain a waterproof coating;

[0034] S5: Bond the face paper, the inner paper, the core paper and the corrugated paper processed into corrugations to obtain a corrugated cardboard box for moisture-proof and compression-resistant packaging; before bonding, the face paper, the inner paper, the core paper and the corrugated paper processed into corrugations are all first coated with a primer coating, with a coating thickness of 6 μm, cured at 90 °C for 4 h, cured at 120 °C for 3 h, then coated with a waterproof coating, with a coating thickness of 25 μm, cured at 60 °C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120 °C for 3 h.

[0035] Comparative Example 1 (changing the coating thickness of the two coatings, and the other method steps are the same as those in Example 1): S1: Take 0.1 part of cetyltrimethylammonium bromide, 0.3 part of trimethylethylammonium bromide, and 1 part of sodium-based nanometer montmorillonite, add them to 15 parts of water, ultrasonically treat for 1 h, heat up to 80 °C, ultrasonically treat for 18 h, wash, filter, and dry to obtain modified montmorillonite; take 2 parts of modified montmorillonite, add 30 parts of ethanol, stir at 20 °C for 2 h, add 25 parts of tetraethoxysilane, stir at 20 °C for 3 h, adjust the pH to 5 with hydrochloric acid, stir at 20 °C for 2 h, filter and wash to obtain a modified composite filler;

[0036] S2: Take 25 parts of silicone-acrylic emulsion, 35 parts of acrylic film-forming emulsion, 20 parts of humidity-sensitive discoloring pigment, 5 parts of modified composite filler, and 1 part of defoaming agent, mix them evenly to obtain a primer coating;

[0037] S3: Add 30 parts of pentaerythritol triacrylate and 12 parts of potassium carbonate into water, stir and disperse. Add 16 parts of o-(trifluoromethyl)benzoyl chloride at 3°C, stir and disperse, then raise the temperature to 25°C and stir for 24 h. Remove the solvent to obtain a fluorine-containing monomer. Take 0.2 part of polyethylene glycol octyl phenyl ether, 0.3 part of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts according to the amount. Drop 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, and 0.6 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion. Take 1 part of n-butyl acrylate, 6 parts of methyl methacrylate, 4 parts of fluorine-containing monomer, 1 part of modified composite filler, and 0.2 part of crosslinking monomer methacrylic acid and drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion. Dissolve 0.08 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution. Dissolve 0.15 part of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution. Under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution and 2 / 5 volume of the core pre-emulsion evenly, raise the temperature to 60°C. When a large amount of blue light appears in the emulsion, keep it warm for 40 min to obtain a seed emulsion. Drop the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution into the seed emulsion, finish dropping in 1 h, then raise the temperature to 65°C and keep it warm for 30 min to obtain a core emulsion. Add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion, finish dropping in 1 h, raise the temperature to 80°C, keep it warm for 60 min, cool, adjust the pH to neutral, and pass through a 200-mesh sieve to obtain an acrylate core-shell emulsion.

[0038] S4: Take 40 parts of silicone-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 25 parts of acrylate core-shell emulsion, 25 parts of modified composite filler, 1 part of photoinitiator 1173, and 1 part of defoamer, mix evenly to obtain a waterproof coating.

[0039] S5: Bond the face paper, inner paper, core paper and corrugated paper processed into corrugated shape to obtain a corrugated cardboard box for moisture-proof and compressive packaging; before bonding, the face paper, inner paper, core paper and corrugated paper processed into corrugated shape are all first coated with a primer coating, with a coating thickness of 2 μm, cured at 90°C for 3 h and at 130°C for 3 h, then coated with a waterproof coating, with a coating thickness of 30 μm, cured at 60°C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120°C for 3 h.

[0040] Comparative Example 2 (changing the coating thickness of the two layers of coatings, and the remaining method steps are the same as those in Example 1): S1: Take 0.1 part of cetyltrimethylammonium bromide, 0.3 part of trimethylethylammonium bromide, and 1 part of sodium-based nanometer montmorillonite, add them to 15 parts of water, ultrasonically treat for 1 h, heat up to 80 °C, ultrasonically treat for 18 h, wash, filter by suction, and dry to obtain modified montmorillonite; Take 2 parts of modified montmorillonite, add 30 parts of ethanol, stir at 20 °C for 2 h, add 25 parts of tetraethoxysilane, stir at 20 °C for 3 h, adjust the pH to 5 with hydrochloric acid, stir at 20 °C for 2 h, filter and wash to obtain modified composite filler;

[0041] S2: Take 25 parts of silicone-acrylic emulsion, 35 parts of acrylic film-forming emulsion, 20 parts of humidity-sensitive color-changing pigment, 5 parts of modified composite filler, and 1 part of defoaming agent, mix evenly to obtain the primer coating;

[0042] S3: Add 30 parts of pentaerythritol triacrylate and 12 parts of potassium carbonate to water, stir and disperse, add 16 parts of o-trifluoromethylbenzoyl chloride at 3 °C, stir and disperse, heat up to 25 °C and stir for 24 h, remove the solvent to obtain a fluorine-containing monomer; Take 0.2 part of polyethylene glycol octyl phenyl ether, 0.3 part of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts by volume; Drop 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, and 0.6 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion; Take 1 part of n-butyl acrylate, 6 parts of methyl methacrylate, 4 parts of fluorine-containing monomer, 1 part of modified composite filler, and 0.2 part of crosslinking monomer methacrylic acid and drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion; Dissolve 0.08 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution; Dissolve 0.15 part of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution; Under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution and 2 / 5 volume of the core pre-emulsion evenly, heat up to 60 °C, when a large amount of blue light appears in the emulsion, keep warm for 40 min to obtain a seed emulsion; Drop the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution into the seed emulsion, finish dropping in 1 h, heat up to 65 °C after dropping, keep warm for 30 min to obtain a core emulsion; Add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion, finish dropping in 1 h, heat up to 80 °C, keep warm for 60 min, cool and adjust the pH to neutral, and sieve through a 200-mesh sieve to obtain an acrylate core-shell emulsion;

[0043] S4: Take 40 parts of silicone-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 25 parts of acrylate core-shell emulsion, 25 parts of modified composite filler, 1 part of photoinitiator 1173, and 1 part of defoaming agent, mix evenly to obtain a waterproof coating;

[0044] S5: Bond the face paper, the inner paper, the core paper, and the corrugated paper processed into corrugated waves to obtain a corrugated cardboard box for moisture-proof and compression-resistant packaging; before bonding, the face paper, the inner paper, the core paper, and the corrugated paper processed into corrugated waves are all first coated with a primer coating, with a coating thickness of 12 μm, cured at 90 °C for 3 h, cured at 130 °C for 3 h, then coated with a waterproof coating, with a coating thickness of 18 μm, cured at 60 °C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120 °C for 3 h.

[0045] Comparative Example 3 (using nano-silica instead of the modified composite filler, and the rest of the method steps are the same as those in Example 1): S1: Take 25 parts of silicon-acrylic emulsion, 35 parts of acrylic film-forming emulsion, 20 parts of humidity-sensitive discoloring pigment, 5 parts of nano-silica, and 1 part of defoamer, and mix them evenly to obtain a primer coating;

[0046] S2: Add 30 parts of pentaerythritol triacrylate and 12 parts of potassium carbonate to water, stir and disperse, add 16 parts of o-trifluoromethylbenzoyl chloride at 3 °C, stir and disperse, heat up to 25 °C and stir for 24 h, remove the solvent to obtain a fluorine-containing monomer;

[0047] S3: Take 0.2 part of polyethylene glycol octyl phenyl ether, 0.3 part of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts according to the amount; add 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, 0.6 part of nano-silica to the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion; take 1 part of n-butyl acrylate, 6 parts of methyl methacrylate, 4 parts of fluorine-containing monomer, 1 part of nano-silica, and 0.2 part of cross-linking monomer methacrylic acid and add them to the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion; dissolve 0.08 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution; dissolve 0.15 part of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution; under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution and 2 / 5 volume of the core pre-emulsion evenly, heat up to 60 °C, when a large amount of blue light appears in the emulsion, keep warm for 40 min to obtain a seed emulsion; add the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution dropwise to the seed emulsion, finish dropping in 1 h, heat up to 65 °C after dropping, keep warm for 30 min to obtain a core emulsion; add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion, finish dropping in 1 h, heat up to 80 °C, keep warm for 60 min, cool, adjust the pH to neutral, and pass through a 200-mesh sieve to obtain an acrylate core-shell emulsion;

[0048] S4: Take 40 parts of silicon-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 25 parts of acrylate core-shell emulsion, 25 parts of nano-silica, 1 part of photoinitiator 1173, and 1 part of defoamer, and mix them evenly to obtain a waterproof coating;

[0049] S5: Bond the face paper, inner paper, core paper, and corrugated paper processed into a corrugated shape to obtain a corrugated cardboard box for moisture-proof and compression-resistant packaging; before bonding, the face paper, inner paper, core paper, and corrugated paper processed into a corrugated shape are all first coated with a primer coating, with a coating thickness of 6 μm, cured at 90 °C for 3 h, cured at 130 °C for 3 h, then coated with a waterproof coating, with a coating thickness of 25 μm, cured at 60 °C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120 °C for 3 h.

[0050] Comparative Example 4 (changing the addition amount of the modified composite filler, and the other method steps are the same as those in Example 1): S1: Take 0.1 part of cetyltrimethylammonium bromide, 0.3 part of trimethylethylammonium bromide, and 1 part of sodium-based nanometer montmorillonite, add them to 15 parts of water, ultrasonically treat for 1 h, heat up to 80 °C, ultrasonically treat for 18 h, wash, filter, and dry to obtain modified montmorillonite; take 2 parts of modified montmorillonite, add 30 parts of ethanol, stir at 20 °C for 2 h, add 25 parts of tetraethoxysilane, stir at 20 °C for 3 h, adjust the pH to 5 with hydrochloric acid, stir at 20 °C for 2 h, filter and wash to obtain the modified composite filler;

[0051] S2: Take 25 parts of silicone-acrylic emulsion, 35 parts of acrylic film-forming emulsion, 20 parts of humidity-sensitive color-changing pigment, 10 parts of modified composite filler, and 1 part of defoaming agent, mix them evenly to obtain the primer coating;

[0052] S3: Add 30 parts of pentaerythritol triacrylate and 12 parts of potassium carbonate into water, stir and disperse. Add 16 parts of o-(trifluoromethyl)benzoyl chloride at 3°C, stir and disperse, then raise the temperature to 25°C and stir for 24 h. Remove the solvent to obtain a fluorine-containing monomer. Take 0.2 part of polyethylene glycol octyl phenyl ether, 0.3 part of sodium dodecyl sulfate, and 15 parts of water, stir evenly to obtain an emulsifier aqueous solution, and divide it into three equal parts by volume. Drop 15 parts of n-butyl acrylate, 1 part of methyl methacrylate, and 0.6 part of modified composite filler into the first part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a core pre-emulsion. Take 1 part of n-butyl acrylate, 6 parts of methyl methacrylate, 4 parts of fluorine-containing monomer, 1 part of modified composite filler, and 0.2 part of cross-linking monomer methacrylic acid, drop them into the second part of the emulsifier aqueous solution, stir and mix, and pre-emulsify for 1 h to obtain a shell pre-emulsion. Dissolve 0.08 part of sodium bicarbonate in the third part of the emulsifier aqueous solution to obtain a buffer aqueous solution. Dissolve 0.15 part of potassium persulfate in 10 parts of water to obtain an initiator aqueous solution. Under nitrogen protection, mix the buffer aqueous solution, 1.5 parts of the initiator aqueous solution, and 2 / 5 volume of the core pre-emulsion evenly, raise the temperature to 60°C. When a large amount of blue light appears in the emulsion, keep the temperature for 40 min to obtain a seed emulsion. Drop the remaining core pre-emulsion and 1.5 parts of the initiator aqueous solution into the seed emulsion within 1 h, raise the temperature to 65°C after dropping, and keep the temperature for 30 min to obtain a core emulsion. Add the remaining initiator aqueous solution and the shell pre-emulsion to the core emulsion within 1 h, raise the temperature to 80°C, keep the temperature for 60 min, cool, adjust the pH to neutral, and sieve through a 200-mesh sieve to obtain an acrylate core-shell emulsion.

[0053] S4: Take 40 parts of silicone-acrylic emulsion, 10 parts of acrylic film-forming emulsion, 25 parts of acrylate core-shell emulsion, 25 parts of modified composite filler, 1 part of photoinitiator 1173, and 1 part of defoamer, mix evenly to obtain a waterproof coating.

[0054] S5: Bond the face paper, inner paper, core paper, and corrugated paper processed into corrugated shape to obtain a corrugated cardboard box for moisture-proof and compression-resistant packaging. Before bonding, the face paper, inner paper, core paper, and corrugated paper processed into corrugated shape are all first coated with a primer coating with a coating thickness of 6 μm, cured at 90°C for 3 h and then cured at 130°C for 3 h, then coated with the waterproof coating with a coating thickness of 25 μm, cured at 60°C for 1 h, irradiated with ultraviolet light for 30 s, and then cured at 120°C for 3 h.

[0055] Performance test: Take the corrugated cardboard boxes prepared in Examples 1 - 2 and Comparative Examples 1 - 4; (1) Test the number of abrasion resistance times with a steel wool abrasion tester; (2) Test the water contact angle; see Table 1 for details.

[0056] Table 1:

[0057] Number of friction resistance Water contact angle / ° Example 1 1368 135 Example 2 1344 133 Comparative Example 1 1142 127 Comparative Example 2 1208 123 Comparative Example 3 1081 114 Comparative Example 4 1220 122

[0058] Conclusion: In Examples 1 and 2, the coating thickness of the two layers was changed. Due to problems such as coating uniformity and stress, the performance decreased in both cases. It can be seen from this that controlling the thickness is of great significance. In Comparative Example 3, nano-silica was used instead of the modified composite filler, resulting in a significant decrease in performance. In Comparative Example 4, the addition amount of the modified composite filler was increased, leading to a decrease in the fluidity of the coating and a decrease in the overall performance due to problems such as crosslinking degree and dispersibility. In summary, the corrugated cardboard box prepared by the present invention has a double-layer coating on its surface, providing good abrasion resistance and waterproofness, and at the same time having good compressive strength.

[0059] Finally, it should be noted that the above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging, characterized in that: The following steps are involved: The surface paper, the inner paper, the core paper and the corrugated paper processed into corrugated paper are bonded together to obtain a moisture-proof and pressure-resistant corrugated paper box for packaging; the surface paper, the inner paper, the core paper and the corrugated paper processed into corrugated paper are coated with a primer and a waterproof coating before bonding; The primer coating comprises the following raw materials, calculated by weight: 20 to 30 parts of silicone-acrylic emulsion, 30 to 40 parts of acrylic film-forming emulsion, 3 to 5 parts of modified composite filler, 15 to 25 parts of moisture-sensitive color-changing pigment, and 1 to 2 parts of defoaming agent; The waterproof coating comprises the following raw materials, calculated by weight: 30 to 40 parts of silicone-acrylic emulsion, 8 to 10 parts of acrylic film-forming emulsion, 20 to 30 parts of acrylate core-shell emulsion, 20 to 30 parts of modified composite filler, 1 to 2 parts of photoinitiator, and 1 to 2 parts of defoamer.

2. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 1, characterized in that: The preparation of the modified composite filler comprises the following steps: Take hexadecyltrimethylammonium bromide, trimethylvinylammonium bromide and sodium montmorillonite, add them into water and ultrasonically treat for 0.5 to 1 hour, heat to 55 to 90°C, ultrasonically treat for 10 to 20 hours, wash, filter and dry to obtain modified montmorillonite; take modified montmorillonite, add ethanol, stir at 20 to 25°C for 2 to 3 hours, add tetraethoxysilane, stir at 20 to 25°C for 2 to 3 hours, adjust the pH to 5 to 6, stir at 20 to 25°C for 2 to 3 hours, filter and wash to obtain a modified composite filler.

3. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 2, characterized in that: The modified montmorillonite comprises the following raw materials, calculated by weight: 0.1-0.2 parts of hexadecyltrimethylammonium bromide, 0.2-0.3 parts of trimethylvinylammonium bromide, 0.8-1.2 parts of sodium montmorillonite, and 10-15 parts of water; the modified composite filler comprises the following raw materials, calculated by weight: 1-2 parts of modified montmorillonite, 20-30 parts of ethanol, and 20-30 parts of tetraethoxysilane.

4. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 1, characterized in that: The preparation of the acrylic ester core-shell emulsion comprises the following steps: The core pre-emulsion is prepared from n-butyl acrylate, methyl methacrylate, modified composite filler and emulsifier aqueous solution; the shell pre-emulsion is prepared from n-butyl acrylate, methyl methacrylate, fluorine-containing monomer, modified composite filler, cross-linking monomer and emulsifier aqueous solution; the acrylate core-shell emulsion is prepared from the core pre-emulsion and the shell pre-emulsion.

5. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 4, characterized in that: The core pre-emulsion includes the following raw materials, calculated by mass: 10 to 15 parts of n-butyl acrylate, 1 to 2 parts of methyl methacrylate, and 0.5 to 1 part of modified composite filler; the shell pre-emulsion includes the following raw materials, calculated by mass: 1 to 2 parts of n-butyl acrylate, 5 to 6 parts of methyl methacrylate, 3 to 4 parts of fluorine-containing monomers, 1 to 1.2 parts of modified composite fillers, and 0.2 to 0.3 parts of cross-linking monomers.

6. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 4, characterized in that: The preparation of the fluorine-containing monomer comprises the following steps: adding pentaerythritol triacrylate and potassium carbonate into water, stirring and dispersing, adding trifluoromethylbenzoyl chloride at 0-5° C., stirring and dispersing, heating to 20-30° C., stirring for 20-30 hours, and removing the solvent to obtain the fluorine-containing monomer.

7. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 6, characterized in that: The fluorine-containing monomer comprises the following raw materials, calculated by weight: 28 to 33 parts of pentaerythritol triacrylate, 10 to 15 parts of potassium carbonate, and 15 to 20 parts of o-trifluoromethylbenzoyl chloride.

8. The method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to claim 1, characterized in that: The coating thickness of the primer is 5 to 8 μm; the coating thickness of the waterproof coating is 20 to 30 μm.

9. A corrugated paper box prepared according to the method for preparing a moisture-proof and pressure-resistant corrugated paper box for packaging according to any one of claims 1 to 8.

Citation Information

Cited By

  • Efficient flame-retardant waterproof and fireproof coating for special humid environment and preparation method of efficient flame-retardant waterproof and fireproof coating

    CN120665494A